The importance of design characteristics in walking from student's perspective: a case study in Universiti Kebangsaan Malaysia - Makki, S.; Surat, M.; Che-Ani, A.l.; Farkisch, H.; Mokhtarian, H.R. (Penerbit UKM, 2012)
Walking is a common form of physical activity, which has a lot of both social and recreational impacts. It is studied as a way of achieving sustainability. Many researchers recommend that walking can increase mental and physical health. Spectators of new urbanism recommend that the good design will encourage walking. There are several characteristics for designing walkable communities, which were frequently described in researches by many authors. In this paper, the four criteria noticed for making walkable university campus include connectivity, accessibility, safety/security and comfort. These criteria have been assessed by gathering survey in the Universiti Kebangsaan Malaysia to find out if these criteria can cause or affect walkability in university campus and it has been supported by previous studies. The result of the survey shows that these criteria are important from students’ perspective as high numbers of the students consider these characters as important for walking activity. The conclusion is to achieve walkable university campus as it will be necessary to evaluate present walking conditions, research walking behavior in different settings and consider these four criteria in designing campus for improving walking condition.